ATP modulation of ATP-sensitive potassium channel ATP sensitivity varies with the type of SUR subunit. - Song, D; Ashcroft, F (2001)
ATP-sensitive potassium (K(ATP)) channels comprise Kir and SUR subunits. Using recombinant K(ATP) channels expressed in Xenopus oocytes, we observed that MgATP (100 microm) block of Kir6.2/SUR2A currents gradually declined with time, whereas inhibition of Kir6.2/SUR1 or Kir6.2DeltaC36 currents did not change. The decline in Kir6.2/SUR2A ATP sensitivity was not observed in Mg(2+) free solution and was blocked by the phosphatidylinositol (PI) 3-kinase inhibitors LY 294002 (10 microm) and wortmannin (100 microm), and by neomycin (100 microm). These results suggest that a MgATP-dependent synthesis of membrane phospholipids produces a secondary decrease in the ATP sensitivity of Kir6.2/SUR2A. Direct application of the phospholipids PI 4,5-bisphosphate and PI 3,4,5-trisphosphate in the presence of 100 microm MgATP activated all three types of channel, but the response was faster for Kir6.2/SUR2A. Chimeric studies indicate that the different responses of Kir6.2/SUR2A and Kir6.2/SUR1 are mediated by the first six transmembrane domains of SUR. The MgATP-dependent loss of ATP sensitivity of Kir6.2/SUR2A was enhanced by the actin filament disrupter cytochalasin and blocked by phalloidin (which stabilizes the cytoskeleton). Phalloidin did not block the effect of PI 3,4,5-trisphosphate. This suggests that MgATP may cause disruption of the cytoskeleton, leading to enhanced membrane phospholipid levels (or better targeting to the K(ATP) channel) and thus to decreased channel ATP sensitivity.